Experimental and Process Modelling Investigation of the Hydrogen Generation from Formic Acid Decomposition Using a Pd/Zn Catalyst - Hafeez, Sanaa; Barlocco, Ilaria; Al-Salem, Sultan M.; Villa, Alberto; Chen, Xiaowei; Delgado, Juan J.; Manos, George; Dimitratos, Nikolaos; Constantinou, Achilleas (My University, 2021)
The use of hydrogen as a renewable fuel has attracted great attention in recent years. The decomposition of formic acid under mild conditions was investigated using a 2%Pd6Zn4 catalyst in a batch reactor. The results showed that the conversion of formic acid increases with reaction temperature and with the formic acid concentration. A process-simulation model was developed to predict the decomposition of formic acid using 2%Pd6Zn4 in a batch reactor. The model demonstrated very good validation with the experimental work. Further comparisons between the 2%Pd6Zn4 catalyst and a commercial Pd/C catalyst were carried out. It was found that the 2%Pd6Zn4 demonstrated significantly higher conversions when compared with the commercial catalyst.
Keywords: Formic acid decomposition; H2 production; Process simulation modelling; Renewable energy; Green chemistry